Human-crocodile conflict in Sukau village, lower Kinabatangan, Sabah - Bala Chandran, Raathi Devi (2019)
Human-crocodile conflicts are increasing due to increase in human population along the Kinabatangan River, Sabah. The conflicts have significant impacts on both human and crocodile populations. This study focussed on addressing the human-crocodile conflicts in Sukau village, Sabah, Malaysia. Objectives of this study were to estimate scale of crocodile conflicts in Sukau village, identify factors that lead to human-crocodile conflicts in Sukau village and determine problems caused by crocodile to the Sukau communities. A total of 90 respondents were obtained in this study. Data were collected by interviews and direct observations. Simple descriptive statistics and Chi-square test were conducted to analyse the data. The main causes of human-crocodile conflicts are deforestation, availability of food sources and existence of oil palm plantation. The main problems caused by crocodiles are damages to the fishing net and treats to people life. During the period from 2006 to 2018, a total of seven individuals were involved in human-crocodile conflict directly. This study suggested that the residents of Sukau village should avoid using the river especially in wet season or night time in order to reduce human-crocodile conflicts.